Developing Private Forest Program to Implement Sustainable Community-Based Forest Management (A Case Study in Malang District, East Java Province) - Cahyo Riyadi; Siti Rochmah; Mardiyono Mardiyono (Indonesian Journal of Environment and Sustainable Development, 2013)
Deforestation still become a problem in Indonesia. Therefore, it needs some effort to overcome the problem, then forestry revitalization is a strategic government policy. One of the targets of forestry revitalization is by building and developing private forests. In 2011, Malang District Forest Service has developed private forest program by Private forest Bussines Group Assistance with a hope that it can realize the sustainable community-based forest management (SCBFM). However, there are many problems in developing private forests in Malang District. This paper tries to describe, to analyze, and to the developing private forest program to the implementation of SCBFM in private forests in Malang district, the result of the developing private forest program in Malang district, and the forthcoming preference of the developing private forest program in malang district to the development of private forest in order to implement SCBFM. Based on the target and realization in the result, there are some obstacles in its implementation. Some constraining factors are human resources factor, budgeting factor, external factor, natural factor, socialization and extension factor. Governmnent’s aid, coordination among agencies, and increasing number of extension worker are required to overcome the problems. Keywords: Deforestation, Private Forest, SCBFM